2014
DOI: 10.1021/nl501152f
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Amorphous FePO4Nanospheres as High-Performance Cathode Material for Sodium-Ion Batteries

Abstract: FePO4 nanospheres are synthesized successfully through a simple chemically induced precipitation method. The nanospheres present a mesoporous amorphous structure. Electrochemical experiments show that the FePO4/C electrode demonstrates a high initial discharging capacity of 151 mAh g(-1) at 20 mA g(-1), stable cyclablilty (94% capacity retention ratio over 160 cycles), as well as high rate capability (44 mAh g(-1) at 1000 mA g(-1)) for Na-ion storage. The superior electrochemical performance of the FePO4/C nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
226
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 54 publications
10
226
0
Order By: Relevance
“…In addition to the abovementioned polyanion compounds, which have already been widely studied for Na‐ion batteries, other polyanion compounds such as carbonophosphates,120, 121, 122 amorphous polyanion compounds,123, 124, 125, 126 and molybdenates,127, 128 have also been researched.…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
“…In addition to the abovementioned polyanion compounds, which have already been widely studied for Na‐ion batteries, other polyanion compounds such as carbonophosphates,120, 121, 122 amorphous polyanion compounds,123, 124, 125, 126 and molybdenates,127, 128 have also been researched.…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
“…Copyright 2014, Nature Publishing Group. (b,c) Reproduced with permission 10. Copyright 2014, American Chemical Society.…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
“…Fang et al also reported a mesoporous amorphous FePO 4 embedded in carbon matrix. The obtained FePO 4 /C exhibited a high initial discharge capacity of 151 mAh g –1 at 20 mA g –1 with stable cyclability (94% capacity retention ratio over 160 cycles) (Figure 8b,c) as well as high rate capability (44 mAh g –1 at 1000 mA g –1 ), and the electrode kept amorphous structure at different states of charge 10. Multi‐walled carbon nanotubes, graphene and carbonized polyaniline decorated FePO 4 were also synthesized with well‐improved electrochemical performances 148, 149, 150, 151.…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to their Li counterparts,1 though sodium‐based system has similar electrochemical reaction characteristics compared to lithium‐based one, the larger ionic radius for sodium ion cause sluggish kinetics and volume change during Na storage, leading to lower capacity, poor cycling and rate properties of the Na storage materials. Recently, major efforts have been devoted to promote the electrochemical performance of Na storage materials, for example, Na x MO 2 ,2, 3, 4, 5, 6, 7, 8, 9, 10 polyanionic framework compounds,11, 12, 13, 14, 15, 16, 17, 18, 19 hexacyanoferrate,20, 21, 22, 23, 24, 25, 26, 27 for the cathode materials, and hard carbons,28, 29, 30, 31, 32, 33 alloys,34, 35, 36, 37, 38, 39, 40, 41 oxides,42, 43 sulfides37, 44, 45, 46 for the anode materials.…”
Section: Introductionmentioning
confidence: 99%